Suscetibilidade in vitro de isolados clínicos de Candida glabrata sensíveis e resistentes ao fluconazol frente à combinações entre fármacos antifúngicos e não antifúngicos - Denardi, Laura Bedin (2013)
Candida species are the most common etiologic agent of opportunistic fungal infections. Candida albicans is the most frequent species in candidiasis, however species of non-albicans species have emerged increasingly in hospitals in which the use of azoles as a prophylactic or therapeutic is common. C. glabrata is the species most relevant in this scenario, causing infections with high morbidity and mortality due to high rates of resistance to antifungal azoles, especially fluconazole, and reduced sensitivity to amphotericin B and echinocandins. The remarkable resistance of these species to antifungal agents requires the search for new therapeutic options. An alternative is the combination of drugs with different mechanisms of action. This study aimed to evaluate the in vitro susceptibility of Candida glabrata to conventional antifungal agents (amphotericin B, ketoconazole, itraconazole, fluconazole and voriconazole), and these associations with non-antifungal drugs (chlorpromazine, linezolid, minocycline, sulfamethoxazole, tacrolimus and diphenyl diselenide). Two groups of clinical isolates of C. glabrata were evaluated. The first group consists of fluconazole-sensitive clinical isolates (FS) (n = 30) and the second, derivative of the first, fluconazole-resistant clinical isolates (FR) (n = 30). Based on protocol M27-A3 (CLSI, 2008), the checkerboard method. In isolation, MICs (Minimum Inhibitory Concentration) for fluconazole ranged from 0.25 to ≥ 64.00 μg/mL (FS) and 64.00 to 256.00 μg/mL (FR); for amphotericin B ranged from 0.06 to 0.50 μg/mL (FS) and 0.03 to 0.50 μg/ mL (FR); for itraconazole 0.50 to 8.00 μg/ mL (FS) and 1.00 to 16.00 μg/mL (FR); for ketoconazole 0.13 to 2.00 μg/mL (FS) and 0.50 to 16.00 μg/mL (FR); for voriconazole 0.13 to 4.00 μg/mL (FS) and 1.00 to 16.00 μg/mL (FR). The combinations of tacrolimus with azoles showed significant synergism rates; for the group FS tacrolimus + ketoconazole (43%), tacrolimus + itraconazole (43%), tacrolimus + voriconazole (37%); for the group FR ketoconazole + tacrolimus (77% ) tacrolimus + itraconazole (73%), tacrolimus + voriconazole (63%). Linezolid combined with ketoconazole and voriconazole showed high rates of synergism against the FR group, 76.67% and 70%, respectively. Minocycline + amphotericin B obtained 46.67% (FS) and 36.67% (FR) of synergism; chlorpromazine + amphotericin B was synergistic for 40% of the FR. Chlorpromazine combined to azoles showed high rates of antagonism for resistant group, 76.67%, 70% and 80% for ketoconazole, itraconazole and voriconazole, respectively, for the sensitive group combinations had higher rates of indifference. Sulfamethoxazole evidenced a higher percentage of indifferent interactions associated with all tested antifungals, 70% (FS), 73.34% (FR) associated to ketoconazole, 60% (FS), 43.34% (FR) associated to itraconazole, 56.67% (FS), 66.67% (FR) ins association with voriconazole, 86.66% (FS), 80% (FR) associated to amphotericin B. Synergistic (76.66%) and indifferent (23.34%) interactions were observed for diphenyl diselenide + amphotericin B combination for the sensitive group. Diphenyl diselenide + fluconazole combination demonstrated indifferent (50%) and antagonistic (40%) interactions for sensitive group, whereas synergistic interactions were observed in 10% of the isolates. The most significant associations deserve in vivo evaluation in order to verify their potential in the treatment of infections caused by C. glabrata.